2002
DOI: 10.1592/phco.22.9.759.34073
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Pharmacist‐Based Smoking‐Cessation Program and Its Impact on Quality of Life

Abstract: We conducted a prospective, open-label trial to evaluate the effectiveness of a pharmacist-based, comprehensive, smoking-cessation program with 31 self-referred subjects. A secondary goal was to measure changes in health-related quality of life (HRQOL) during the cessation attempt. The program consisted of weekly, 1-hour group sessions over 12 weeks. It incorporated nicotine replacement therapy (patch, gum) with extensive behavior modification counseling. Trained pharmacists served as program facilitators. Smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 34 publications
2
50
2
1
Order By: Relevance
“…This is also consistent with results suggested by Tonnesen where a 1-year abstinence rate of 25% should be expected from a smoking cessation programme 6 . While most of the studies showed a decrease in abstinence rate over time [11][12][13][14][15] , our study demonstrated a significant increase (P<0.05) in abstinence rate from clinic completion (19.8%) to both 6-(23.8%) and 12-month (25.4%) followup. This is consistent with the results found by Philbrick and colleagues who reported an increase in abstinence rate from 47.6% to 52.4% at 3 and 6 months respectively 16 and also the pilot study performed in CGH previously 7 .…”
Section: Discussioncontrasting
confidence: 65%
“…This is also consistent with results suggested by Tonnesen where a 1-year abstinence rate of 25% should be expected from a smoking cessation programme 6 . While most of the studies showed a decrease in abstinence rate over time [11][12][13][14][15] , our study demonstrated a significant increase (P<0.05) in abstinence rate from clinic completion (19.8%) to both 6-(23.8%) and 12-month (25.4%) followup. This is consistent with the results found by Philbrick and colleagues who reported an increase in abstinence rate from 47.6% to 52.4% at 3 and 6 months respectively 16 and also the pilot study performed in CGH previously 7 .…”
Section: Discussioncontrasting
confidence: 65%
“…49 Furthermore, smoking cessation programs using behavioral modification along with bupropion or nicotine replacement have resulted in improved physical healthand mental health-related quality of life. 49,61 Therefore, we encourage a comprehensive smoking cessation program in patients with chordoma who are current smokers at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…390 This program consisted of nicotine replacement therapy (gum or transdermal patch) and 1-hour, pharmacist-facilitated counseling and behavior modification sessions offered to 31 self-referred patients during 12 weeks. Abstinence rates at 3 and 6 months were 42% and 26%, respectively.…”
Section: Documented Impactmentioning
confidence: 99%